The Influence of Supervision and Work Environment on the Work Effectiveness of Police Members at the Situraja Police Section, Sumedang Resort Police - Agus Permana; Enjang Sudarman; Sukiman Sukiman (Dinasti Publisher, 2026)
The purpose of the study is to describe and analyze the influence of supervision on the effectiveness of the work of members, the influence of the work environment on the effectiveness of the work of members, To analyze the influence of supervision and the work environment together on the effectiveness of the work of members of the Situraja Police Sector. The results of the t test showed a calculated t value of 5.354 greater than the t table of 2.014 at a significance level of 0.05, The results of the t test showed a calculated t value of 4.903 greater than the t table of 2.014 , so that the hypothesis stating that there is an influence of the work environment on the effectiveness of the work of members is accepted, The results of the F test showed a calculated F value of 60.914 greater than the F table of 2.81 with a significance level of 0.000 <0.05 , so that the simultaneous hypothesis is accepted . This means that the combination of effective supervision and a conducive work environment together can increase the effectiveness of the work of members of the Situraja Police Sector . The Adjusted R Square value of 0.731 indicates that 73.1% of the variation in the effectiveness of member work can be explained by the variables of supervision and work environment , while 26.9% is influenced by other factors not examined in this study, such as leadership, work motivation, work discipline, competence, and organizational culture